Phenology of shrubby species from Rosaceae Juss. in the Livoberezhne Polissya (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
Phenology has been studied in 20 species of shrubby species of Rosaceae in Livoberezhne Polissia. The main phenological phases are prolonged with higher effective temperature; the data on particular phases are shown. Investigated plants have highly adaptive abilities and may be recommended for wide use in Northern Ukraine.
Keywords: Livoberezhne Polissia, climatic conditions, phenology, Rosaceae.